effect of silver diamine fluoride on caries induced in Wistar rats - Vanegas, Susana; Godoy, Astrid; Urdaneta, Leonidas; Olávez, Daniela; Padrón, Karla; Solórzano, Eduvigis (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: dental caries is considered a public health problem. Various biomaterials have been suggested for treating it, including fluride+silver nitrate mix, known as silver diamine fluoride (SDF) which contains cariostatic, remineralizing, and bactericide properties and is used on primary teeth. Only a few studies have assessed the response of dental tissue when this substance is applied; the objective of this study was therefore to determine the effect of SDF on caries induced in Wistar rats. Methods: dental caries was induced in Wistar rats’ molars by inoculating them with S. mutans CVCM656 and feeding them a sucrose-rich diet for 12 weeks. Once caries were diagnosed and sorted out into control groups (C1, C2) and experimental groups (E1, E2), softened dentine was removed from molars; only the molars from experimental groups received a topical application of 3.8% SDF. Finally, clinical assessment was performed and samples were collected for histological study 7 and 13 weeks after treatment. Results: the control groups experienced an increased number of carious lesions and progression in severity, while the same parameters in the experimental groups remained unchanged, showing hard dark dentine surfaces. The histological report showed increased predentine thickness in molars from the experimental groups only. Conclusions: the protocol of caries induction in Wistar rats was successful. Treatment with SDF deactivated the carious processes, arresting not only severity progression but also the increase in number of caries; these findings may be extrapolated to humans.